PENYALAHGUNAAN DANA KARTU INDONESIA PINTAR KULIAH DAN DAMPAKNYA TERHADAP PENDIDIKAN DI INDONESIA - Irene Dwi Ardianty; Syafiq Febriyanto; R.Aj Cahya Dira Aulia Putri; Ardiya Pramesti Regita Cahyani; Mohamad Djasuli (LPPM STIH Awang Long, 2024)
The Indonesian Smart College Card (KIP) scholarship program is a refinement of the Poor Student Assistance (BSM) program which is a scholarship provided by the government to help underprivileged prospective students continue their education. In line with Indonesia's national goal to make the nation's life smarter. The government provides financial assistance in the form of education costs to recipients so that they are used as effectively and efficiently as possible as a form of implementation of the government's 12-year compulsory education program. This research aims to find out the impact and influence of misuse in the implementation of the Smart Indonesia Card (KIP) program. The results of this research state that the use of scholarship funds has been utilized properly, but there are still many perpetrators of violations in the misuse of KIP-K funds which are not in accordance with educational objectives. Environmental influences use funds to fulfill a hedonistic lifestyle, wrongly targeted recipients and obstacles in fulfilling complex requirements and applications.